A Unique Type or Variation of Bile Duct Cyst in a 9-Year-Old Girl:A Remarkable Case Study - Paņina, Aleksandra; Zviedre, Astra; Laizāns, Paulis; Apine, Ilze (Acta medica Lituanica, 2023)
Patients with bile duct cysts require careful radiological assessment of the hepatobiliary system prior to surgical intervention. This clinical case is uncommon with an atypical clinical presentation and radiological findings. According to the most widely used classification of choledochal cysts, this case presents a combination of Type I and Type IV of choledochal cyst (CC) combining the form of extra, intrahepatic bile ducts and cystic duct dilations.
Keywords: bile duct cyst; Roux-en-Y hepaticojejunostomy; common bile duct; choledochal cyst